Strategies for attaining the 4th goal of sustainable development in public secondary schools in Anambra State (West African Journal on Sustainable Development, 2024)
The study investigated the strategies used by teachers in attaining the 4th goal of sustainable development in public secondary schools in Anambra State. Sustainable Development Goal 4 is a broad objective that ensures that every child irrespective of creed, gender, and social status gets quality primary and secondary education. The aim of the study was to find out the strategies employed by school teachers to ensure that every student in their schools acquires quality education for lifelong learning. The descriptive research design was used for the study, and the study population comprised 6402 secondary school teachers in Anambra State. Two research questions guided the study and the multi-stage sampling technique was used to select 994 teachers. A structured questionnaire was used for data collection and validated by three Education experts. The reliability of the instrument was done using Cronbach alpha which yielded a Coefficient value of 0.85. Mean scores and standard deviation were used to analyze the data collected. The findings revealed that teachers rarely use inclusive teaching and guided learning strategies in achieving sustained development goal 4. The study recommended that teachers should be trained and retrained on the act of inclusive teaching and learning for quality education.
Keywords: strategies; sustaining development; inclusive education; quality education; school teachers